STRATEGI PENGGUNAAN TEKNOLOGI PEMBELAJARAN UNTUK PENINGKATAN BERPIKIR KRITIS SISWA - Rusiadi (CV. Adiba Aisha Amira, 2024)
This research discusses effective strategies for utilizing learning technology to improve students' critical thinking abilities. The main focus of research is the use of online learning platforms, interactive digital content, virtual and augmented reality simulations, and learning analytics. Online learning platforms enable active interaction through discussion forums, while interactive digital content such as videos and online quizzes stimulate conceptual understanding and in-depth analysis. Virtual simulations and augmented reality provide real-world experiences, while learning analytics leverage data to customize learning and monitor student progress. Through this combination of strategies, it is hoped that students can develop critical thinking skills effectively, preparing them to face challenges in the modern educational era.